Impact of Information Communication Technology Competency Among Auditing Professionals - M. M. Thottoli (Учёт. Анализ. Аудит)
The objective of this study is to find out the influence of Impact of Information Communication Technology competencies and Information Communication Technology Training among auditing professionals. This paper proposes a defined set of survey questionnaires to measure Information Communication Technology (ICT) competency and ICT Training variables. The sample size focuses on junior qualified professional auditors who were selected based on their experience in the field of accounting or auditing. The sample of population consists of individual practicing auditors from small audit firms in Kerala. Data were analyzed using partial least squares structural equation modeling approach (PLS-SEM). Expectedly, ICT competencies among auditing professionals and their ICT training are imperative among junior auditing professionals for auditing in a computer-based environment. The impact of audit efficiencies, ensuring client's fair financial statements, and timeliness of audit tasks were achieved by auditing professionals with ICT competencies and ICT training. This is important not only for junior staff, but also for lead auditors who have the authority to sign audit reports. The value of the research studies lies with a comprehensible examination of findings of various previous studies and enlightened commentaries on ICT enabled audit practice by sole proprietorship practicing audit firms, mainly in rural locations. In addition, such scientific method of understanding the implications of ICT enables auditing which involved in auditing professional policy makers intervention.